2017
DOI: 10.1152/ajpregu.00461.2016
|View full text |Cite
|
Sign up to set email alerts
|

Long-term HIF-1α transcriptional activation is essential for heat-acclimation-mediated cross tolerance: mitochondrial target genes

Abstract: An important adaptive feature of heat acclimation (HA) is the induction of cross tolerance against novel stressors (HACT) Reprogramming of gene expression leading to enhanced innate cytoprotective features by attenuating damage and/or enhancing the response of "help" signals plays a pivotal role. Hypoxia-inducible factor-1α (HIF-1α), constitutively upregulated by HA (1 mo, 34°C), is a crucial transcription factor in this program, although its specific role is as yet unknown. By using a rat HA model, we studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 47 publications
0
13
0
3
Order By: Relevance
“…In the rat, a HIF-1α dimerization blockade was also conducted during the entire 1 month HA session. We have shown that a continuous HIF-1α dimerization blockade is needed to attenuate HACT, even though no changes in acclimatory levels of HSP72 were measured (Alexander-Shani et al, 2017 ). his attenuation adds metabolic aspects to HACT.…”
Section: Hact: Constitutive Injury Attenuation—a Lesson From the Ischmentioning
confidence: 99%
See 4 more Smart Citations
“…In the rat, a HIF-1α dimerization blockade was also conducted during the entire 1 month HA session. We have shown that a continuous HIF-1α dimerization blockade is needed to attenuate HACT, even though no changes in acclimatory levels of HSP72 were measured (Alexander-Shani et al, 2017 ). his attenuation adds metabolic aspects to HACT.…”
Section: Hact: Constitutive Injury Attenuation—a Lesson From the Ischmentioning
confidence: 99%
“…In retrospect, the experimental series in which the magnitude of HACT was measured (e.g., infarct size) during blockade of HIF-1α dimerization and HSP72 augmentation, serve as examples of the integrated beneficial effects needed to achieve HACT. More recently, experiments involving HIF-1α mitochondrial target genes demonstrated the positive contribution of HIF-1α to HACT by shifting pyruvic acid away from the mitochondria to enhance glycolysis (Alexander-Shani et al, 2017 ). The beneficial effects of HA in experimental animal models will be further discussed below (see “ Phenotypic plasticity underlying HACT—a broad perspective” ).…”
Section: Hact: Constitutive Injury Attenuation—a Lesson From the Ischmentioning
confidence: 99%
See 3 more Smart Citations